(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Transport potential is one of the indicators determining the level of development of the region. Transport services have a direct impact on the size of the region’s gross domestic product. In this article, the transport potential of the region in the northern part of the republic, its current state and directions of development were shown. In the article, an algorithm for evaluating the transport potential of the economic region was developed. Proposals have been developed that lead to the development of the transport potential of the region and the increase in the volume of transport services.